Body Languages: Art as an alternative teaching method to promote inclusivity and equality in education - Fernández Hoya, Gema (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2022)
This article examines how the education system and education through art can work together to build schools that are both democratic and inclusive. To this end, we will consider a specific case study: an arts education programme run by the Lisarco Collective at the CEIP Trabenco public school. The Lisarco Collective is a group of artists with and without disabilities, and at the time of this study, the CEIP Trabenco school was a centre with particular provision for pupils with special educational needs. Our principal research objectives were to consider the links between formal education and so-called Art Thinking, and to identify the effects of the Lisarco programme on the participants in our case study. We approached these aims in two ways, firstly through an analysis and synthesis of the literature in this field followed by a quantitative study involving a questionnaire-based survey of the CEIP Trabenco educational community. Our results show that students included in this art-education programme internalised the principles of equality and respect for diversity and achieved improvements both academically and personally. Indeed, the Lisarco led intervention appears to benefit all project partners. In conclusion, this work shows that artistic activity is a viable alternative teaching method that both addresses student’s education wholistically and promotes inclusivity.